2021
DOI: 10.29393/gp2-3mesr10003
|View full text |Cite
|
Sign up to set email alerts
|

Mujeres en Espacios De Decisión. Escenario Actual en Las Universidades Estatales Chilenas

Abstract: Estas instituciones tienen múltiples funciones orientadas en construir y compartir conocimientos, contribuyendo en el fortalecimiento de la democracia y el desarrollo de la sociedad. No obstante, como instituciones no están exentas de dinámicas estereotipadas en los ámbitos disciplinares y organizacionales, dejando en una posición de subrepresentación a las mujeres en espacios de toma de decisiones, por lo que las funciones desarrolladas por las Universidades se efectúan desde un solo punto de vista.Por lo ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, this increase in enrollment by women in higher education does not lead to greater women representation in leadership and decision-making positions. For example, in the field of education, a study by Riquelme [2], found that the number of woman rectors at Chilean universities belonging to the Consortium of State Universities of Chile (CUECH, in its Spanish acronym) is only 16.7%. According to the data, these leadership positions are highly dominated by men, meaning there is an overrepresentation of males in said positions.…”
Section: Introductionmentioning
confidence: 99%
“…However, this increase in enrollment by women in higher education does not lead to greater women representation in leadership and decision-making positions. For example, in the field of education, a study by Riquelme [2], found that the number of woman rectors at Chilean universities belonging to the Consortium of State Universities of Chile (CUECH, in its Spanish acronym) is only 16.7%. According to the data, these leadership positions are highly dominated by men, meaning there is an overrepresentation of males in said positions.…”
Section: Introductionmentioning
confidence: 99%